Comparative Analysis of Different Cutting Milling Strategies Applied in Duplex Stainless Steel - Amaro, Paulo (2020)
It is well known that the duplex stainless steels are considered to be difficult-to-machine because of its high toughness, low thermal conductivity, and high degree of work hardening. When machining this type of materials, the tools presents an irregular wear and often occur a built-up edge (BLUE) [1]. This work studies the influence of cutting milling strategy in the machinability of these alloys, comparing conventional and trochoidal toolpaths, milled with a tool that have interchangeable inserts coated with AlTiN. Concerning to the cutting parameters, the values recommended by the tool manufacturer (90-120 m/min.) were applied to the conventional milling strategy, while for the trochoidal milling strategy were applied higher cutting speeds, in a range of 120 to 300 m/min. For both strategies, the results shown that the tool edge damage is characterized by a progressive development of a flank wear, followed by chipping phenomenon, that usually first appear localized in the region of the cutting edge where the contact with the chip ends. As the machining continues, a non-uniform chipping appears along the cutting edge. For the conventional milling strategy, the best results were obtained for the cutting speed of 120 m/min, with a material removal rate of 17,16 cm3/min. and a tool life of 20 minutes. For the trochoidal strategy, it is possible to double the cutting speed (240 m/min), maintaining the same tool life time (20 min.), and increasing the material removal rate up to 23,66 cm3/min.